2020
DOI: 10.1364/ome.399502
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of tetragonal and orthorhombic Sn1-xBaxO2 nanostructures via the spray pyrolysis method

Abstract: A single and mixed-phases SnO2 (M-SnO2) nanostructures were synthesized by a simple spray pyrolysis method. The nanostructural crystallinity, surface morphology and optical evolution of Ba-doped tetragonal phase SnO2 with different Ba contents were studied by x-ray diffraction, atomic force microscopy, ultraviolet-visible spectroscopy and photoluminescence spectral measurements. The M-SnO2 with orthorhombic as well as tetragonal phases are formed in 6% Ba-doped SnO2 sample and it exhibits the highest average t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…01-079-0613) in the first configuration, due to the occurrence of MIC forming poly:Si) . There is other three peaks at 2θ = 34°, 38°, and 44°, corresponding to tetragonal SnO 2 (101), SnO 2 (111) (JCPDS File Card No 41-1445) and GeO 2 (201) (JCPDS File Card No. 43-1016), respectively, due to the annealing at slightly low levels of vacuum that cause partial oxidation of Ge and Sn .…”
Section: Resultsmentioning
confidence: 99%
“…01-079-0613) in the first configuration, due to the occurrence of MIC forming poly:Si) . There is other three peaks at 2θ = 34°, 38°, and 44°, corresponding to tetragonal SnO 2 (101), SnO 2 (111) (JCPDS File Card No 41-1445) and GeO 2 (201) (JCPDS File Card No. 43-1016), respectively, due to the annealing at slightly low levels of vacuum that cause partial oxidation of Ge and Sn .…”
Section: Resultsmentioning
confidence: 99%
“…There are other three peaks at 2θ = 34°, 38° and 44° corresponding to SnO 2 (101), SnO 2 (200) (JCPDS Card No 41-1445) and GeO 2 (201) JCPDS (card no. , respectively due to the annealing at slightly low level of vacuum that causes partially oxidation of Ge and Sn [19,20]. On the other hand, the con gurations deposited on n-Si and p-Si show highly oriented poly-GeSn crystallites at (400) direction of 2θ = 62°.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that magnesium (Mg) doping can effectively reduce the quenching sites on ZnO surface. , Tin oxide (SnO 2 ) is also an important semiconductor having wide bandgap ( E g ) between 3.5 and 3.8 eV depending on experimental results and theoretical estimations . To make SnO 2 suitable for ETLs and modulate the physical properties, several groups have explored dopants such as europium (Eu), indium (In), antimony (Sb), strontium (Sr), cobalt (Co), barium (Ba), neodymium (Nd), etc. Recently, barium stannate (BaSnO 3 ) has been explored as an ETL material for optoelectronic devices due to its excellent properties such as large bandgap, relatively high electron mobility, and suitable energy level. It was reported that the optical and electrical properties of BaSnO 3 can be modulated by doping with Zn, La, Sb, or F .…”
mentioning
confidence: 99%
“…It is observed that the BSO films show broader absorption in the wavelength region between 300 and 800 nm with increasing the Ba:Sn ratio. The optical bandgap of the BSO films was estimated from Tauc plots drawn from UV–vis absorption spectra, using (α h ν) = hν – E g , where α is the absorption coefficient, h Planck’s constant, ν the frequency, and E g the bandgap energy . The estimated bandgap values of BSO were 3.02, 3.08, 3.14, 3.37, 3.44, and 3.71 eV for the BSO films with Ba:Sn ratios of 0.50:0.50 (i.e., BaSnO 3 ), 0.42:0.58, 0.31:0.69, 0.21:0.79, 0.10:0.90, and 0.00:1.00 (i.e., SnO 2 ), respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation